Lap Joint Carbon Steel ST 37 and Aluminum 6061 with Friction Stir Welding (FSW) - Setiawan, Widia; Darmadi, Djarot B.; Suprapto, Wahyono; Soenoko, Rudy (Universitas Muhammadiyah Surakarta, 2016)
In this research, Aluminum 6061 and Carbon steel ST 37 sheet were lap joined by friction stir welding. A hardened medium carbonese steel (EMS 45) was used as rotary Probe. The microstructures of the joining inter-metallic compounds were observed by scanning electron microscopy, microstructure photograph, and micro-hardness tests. The joint strength was evaluated by shear stress tests. The experiment was performed with varied length of pin probe 6, 7, and 8 mm, equal rotational speed of 2500 rpm, and welding speed (15 mm/minutes). The Inter-metallic compounds of aluminums sheet was cut off the pin probe and the mixture on the Carbon steel ST 37. Intermetallic compounds were analyzed on its micro sructure in this region aluminum and carbon steel mixed, the value joint tensile shear 6.2KN.